Pengaruh Loan To Deposit Ratio, Non Performing Loan, Net Interest Margin Dan Biaya Operasional / Pendapatan Operasional Terhadap Return On Asset Pada Bank Umum Swasta Nasional Devisa Yang Terdaftar Di BEI Tahun 2019-2021 - M Arif Syaifulloh; Budi Wahono; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this research to determine the influence of Loan to Deposit Ratio, Non-Performing Loan, Net Interest Margin and Operational Cost of Operational Income towards Return On Asset of National Private Foreign Exchange Commercial Banks listed on the BEI in 2019-2021. The data used in this study is secondary data. The population used is National Private Foreign Exchange Commercial Banks at BEI for the period 2019-2021. The sampling technique was done by purposing sampling method. The sample of this research is 16 companies. Data analysis was done by using multiple linier regression method. The result of this study indicate that (1) Loan to Deposit has no effect on ROA, with a significance level of 0,534 > 0,05. (2) Non-Performing Loan has a segnificant negative effect on ROA, with a significance level of 0,018 < 0,05. (3) Net Interest Margin has a segnificant positive effect on ROA, with a significance level of 0,045 < 0,05. (4) Operating Costs Operating Income has a segnificant negative effect on ROA with a significance level of 0.000 <0.05. Keywords: Loan to Deposit Ratio, Non Performing Loan, Net Interest Margin, Operating Costs Operating Income and Return On Asset